Clinical Profile and Treatment Outcomes of Hypermanganesemia with Dystonia 1 and 2 among 27 Indian Children. Issue 7 (12th August 2022) - Garg, Divyani; Yoganathan, Sangeetha; Shamim, Uzma; Mankad, Kshitij; Gulati, Parveen; Bonifati, Vincenzo; Botre, Abhijeet; Kalane, Umesh; Saini, Arushi Gahlot; Sankhyan, Naveen; Srivastava, Kavita; Gowda, Vykuntaraju K.; et al.
ABSTRACT: Background: Hypermanganesemia with dystonia 1 and 2 (HMNDYT1 and 2) are rare, inherited disorders of manganese transport. Objectives: We aimed to describe clinical, laboratory features, and outcomes among children with HMNDYT. Methods: We conducted a retrospective multicenter study involving tertiary centers across India. We enrolled children between 1 month to 18 years of age with genetically confirmed/clinically probable HMNDYT. Clinical, laboratory profile, genetic testing, treatment details, and outcomes scored by treating physicians on a Likert scale were recorded. Results: We enrolled 27 children (19 girls). Fourteen harbored SLC30A10 mutations; nine had SLC39A14 mutations. The SLC39A14 cohort had lower median age at onset (1.3 [interquartile range (IQR), 0.7–5.5] years) versus SLC30A10 cohort (2.0 [IQR, 1.5–5.1] years). The most frequent neurological features were dystonia (100%; n = 27), gait abnormality (77.7%; n = 21), falls (66.7%; n = 18), and parkinsonism (59.3%; n = 16). Median serum manganese (Mn) levels among SLC39A14 (44.9 [IQR, 27.3–147.7] mcg/L) cohort were higher than SLC30A10 (29.4 [17.1–42.0] mcg/L); median hemoglobin was higher in SLC30A10 (16.3 [IQR, 15.2–17.5] g/dL) versus SLC39A14 cohort (12.5 [8.8–13.2] g/dL). Hepatic involvement and polycythaemia were observed exclusively in SLC30A10 variants. A total of 26/27 children underwent chelation with disodium calcium edetate. Nine demonstrated some improvement, three stabilized, two had marked improvement, and one had normalization. Children with SLC39A14 mutations had poorer response. Two children died and nine were lost to follow‐up. Conclusions: We found female predominance. Children with SLC39A14 mutations presented at younger age and responded less favorably to chelation compared to SLC30A10 mutations. There is emerging need to better define management strategies, especially in low resource settings.